2000
DOI: 10.1097/00001756-200007140-00052
|View full text |Cite
|
Sign up to set email alerts
|

Methylmalonate administration decreases Na+,K+-ATPase activity in cerebral cortex of rats

Abstract: Buffered methylmalonate (MMA) was injected s.c. into rats twice a day at 8 h intervals from 5 to 25 days of age (chronic treatment), or into 10-day-old rats three times a day at 1 h intervals (acute treatment). Control rats received saline in the same volumes. Na+,K+-ATPase and Mg2+-ATPase activities were determined in the synaptic plasma membranes from cerebral cortex of rats. Na+,K+-ATPase activity was reduced by 30-40% in MMA-treated rats, whereas Mg2+-ATPase activity was not. In contrast, MMA at final conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(50 citation statements)
references
References 5 publications
3
47
0
Order By: Relevance
“…An effect on the malate carrier at higher concentrations might be theoretically interesting; however, it is questionable whether this effect has any relevance for the pathophysiology of methylmalonic acidurias. Apart from this, MMA was shown to inhibit pyruvate carboxylase (34) and Na ϩ /K ϩ -ATPases (35).…”
Section: Discussionmentioning
confidence: 99%
“…An effect on the malate carrier at higher concentrations might be theoretically interesting; however, it is questionable whether this effect has any relevance for the pathophysiology of methylmalonic acidurias. Apart from this, MMA was shown to inhibit pyruvate carboxylase (34) and Na ϩ /K ϩ -ATPases (35).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MMA loading decreases the ATP/ADP ratio in neuronal rat cultures and, concomitantly, the resting membrane potential (13). Furthermore, it has been shown that MMA decreases Na ϩ /K ϩ -ATPase activity (42). Consequently, membrane depolarization in general and the removal of the voltage-dependent Mg 2ϩ block of NMDA receptors in particular, results in an unimpeded influx of Ca 2ϩ and Na ϩ into neurons in general (43,44), and after MMA loading in particular (13).…”
Section: Discussionmentioning
confidence: 99%
“…MMA has been demonstrated to provoke behavioral alterations, seizures and striatal lesions in rats after intrastriatal administration through activation of glutamate receptors, energy depletion and oxidative damage (de Mello et al 1996;Wyse et al 2000;Fighera et al 2003;Malfatti et al 2003;Ribeiro et al 2005;Royes et al 2003Royes et al , 2005Royes et al , 2006Furian et al 2007). Other experimental studies confirmed that impairment of brain mitochondrial energy metabolism, alterations of the redox status and glutamatergic neurotransmission may represent important pathomechanisms of MMA neurotoxicity (Wajner and Coelho 1997;McLaughlin et al 1998;Fontella et al 2000;Kölker et al 2000;Brusque et al 2001Brusque et al , 2002Okun et al 2002;Malfatti et al 2003;Pettenuzzo et al 2006).…”
Section: Introductionmentioning
confidence: 98%